2018
DOI: 10.31413/nativa.v6i6.6802
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano Chelated Nitrogen and Urea Fertilizers on Wheat Plant Under Drought Stress Condition

Abstract: This study was performed to evaluation of nano chelated nitrogen and urea fertilizers on wheat plant under drought stress condition. Experiments were carried out in two locations in Fars province, Iran. Experimental design was performed as split-split plot in RCBD design. The first factor included irrigation treatments (normal and withholding irrigation at flowering stage), sub factor was nitrogen treatment (0, 37, 74 and 110 kg.ha -1 ) in the form of Urea fertilizer, and sub-sub factor was nitrogen (0, 14, 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Application of RDN (T 2 ) recorded significantly the lowest length, breadth and weight of ear head, grain yield plant -1 and grain yield (kg ha -1 ). The results of this investigation are consonance with the findings of Al-juthery et al (2018) [1] and Astaneh et al, (2018) [2] , and Salama and Bandry (2020) [9] . The maximum harvest index (31.84%) was recorded with the application of 75% RDN through urea as soil application + 25% RDN through 1 spray of nano-urea (45 DAS) (T 5 ) which was found at par with the application of 75% RDN through urea as soil application + 25% RDN through one spray of urea (45 DAS) (T 8 ) and 50% RDN through urea as soil application + 50% RDN through two spray of nano-urea (30, 45 DAS) (T 4 ) (Table 1).…”
Section: Effect Of N-nano Fertilizer On Yield Attributes and Yield Of...supporting
confidence: 93%
“…Application of RDN (T 2 ) recorded significantly the lowest length, breadth and weight of ear head, grain yield plant -1 and grain yield (kg ha -1 ). The results of this investigation are consonance with the findings of Al-juthery et al (2018) [1] and Astaneh et al, (2018) [2] , and Salama and Bandry (2020) [9] . The maximum harvest index (31.84%) was recorded with the application of 75% RDN through urea as soil application + 25% RDN through 1 spray of nano-urea (45 DAS) (T 5 ) which was found at par with the application of 75% RDN through urea as soil application + 25% RDN through one spray of urea (45 DAS) (T 8 ) and 50% RDN through urea as soil application + 50% RDN through two spray of nano-urea (30, 45 DAS) (T 4 ) (Table 1).…”
Section: Effect Of N-nano Fertilizer On Yield Attributes and Yield Of...supporting
confidence: 93%
“…The higher nitrogen concentration of grain and straw with increasing nitrogen rate might be due to the crop's having adequate nitrogen, which could enhance nitrogen concentration on biological yield, particularly straw, due to better roots and greater density. These is in line with the findings of Worku et al (2007) and Astaneh (2018) who reported that increase in the supply of nitrogen increases straw nitrogen content gradually.…”
Section: Nitrogen Content Nitrogen Uptake and Nitrogen Use Efficiencysupporting
confidence: 93%
“…Furthermore, the application of NP S improves carbon balance in crops, accelerates plant growth, can increase the efficiency of micro and macronutrients of plants, and reducing the use of chemical fertilizers per unit area which causes environmental problems (Mahil & Kumar, 2019;Hasan & Saad, 2020). Most of the researches conducted globally on nano-fertilizers suggest that these materials have a greater role in crop production with environmental safety, ecological sustainability and economic stability, the same as reported by Abdel-Aziz et al (2016) Astaneh et al (2018) found that Nano Chelated N is the best fertilizer due to the significant yield increase of wheat in lesser doses. Fertilization with NPK NPs produced an increase in yield for wheat (Abdelsalam et al, 2019).…”
Section: Introductionmentioning
confidence: 67%
“…13, 22.90 and 30.86%, 4.31, 7.78 and 10.08% , 4.33, 7.29 and 10.34% and 13.41, 29.03 and 40.71% in the same order compared to control treatment (NF 1 ). Application of 14, 27 and 41kg ha -1 nano-fertilizer led to 31, 44 and 98% increase in seed yield compared to control (Astaneh et al, 2018). Fertilization with NPK NPs produced an increase in yield for wheat (Abdelsalam et al, 2019).…”
Section: Effect Of Nano-fertilizermentioning
confidence: 90%